2002
DOI: 10.1243/095765002760024881
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of flow and cavitation characteristics of a two-step throttle in water hydraulic valves

Abstract: In hydraulic power systems with water hydraulic valves, cavitation is more likely to happen than in an oil hydraulic system. A two-step throttle, which consists of two ori ces, is an effective way to avoid or reduce cavitation damage. In this research, experiments are conducted to investigate the ow-pressure and cavitation characteristics of throttles of different shapes. The working medium is tap water. A new indicator is introduced to detect cavitation inception, namely that a particular low-frequency compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…10 Schematic diagram of the testing apparatus Low cavitation in water hydraulic two-stage throttle poppet valve two-stage throttle valve with a low critical cavitation index level exhibits a better anti-cavitation capability than the single-stage throttle valve. This is consistent with the qualitative conclusions as drawn by Oshima et al [14] and Liu et al [15,16]. Indeed, the multi-stage throttles are beneficial for improving the system's anti-cavitation capability.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…10 Schematic diagram of the testing apparatus Low cavitation in water hydraulic two-stage throttle poppet valve two-stage throttle valve with a low critical cavitation index level exhibits a better anti-cavitation capability than the single-stage throttle valve. This is consistent with the qualitative conclusions as drawn by Oshima et al [14] and Liu et al [15,16]. Indeed, the multi-stage throttles are beneficial for improving the system's anti-cavitation capability.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that the discharge coefficient and the critical cavitation number for water poppet throttles were considerably different from those of oil ones, due to the high density and low viscosity of water. Recently, Liu et al [15,16] investigated experimentally the flow and cavitation characteristics of a two-stage throttle in water hydraulic system; they concluded that the two-stage throttle had stronger anti-cavitation capability than the single-stage one, and that the shape of seats also affected the anticavitation capability of the throttles. The cavitation choking appeared only when cavitation index was less than 0.4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that the anticavitation performance of the sharp-edged two-step throttle valve is better than the chamfer-edged one. 20 Furthermore, the pressure distribution of two-step throttle valve has been investigated through numerical simulation. The simulation results evidences that a high backpressure is beneficial for improving the properties of anticavitation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when a pressure shock occurs, it generates a large impact flow caused by the external load. This leads to a serious cavitation [13][14][15] phenomenon, poor reliability and unstable dynamic characteristics. These problems seriously affect the safety and reliability of the pilot operated check valve and associated system.…”
Section: Introductionmentioning
confidence: 99%